Glacial Earthquakes and Precursory Seismicity Associated With Thwaites Glacier Calving. Issue 3 (3rd February 2020) - Winberry, J. Paul; Huerta, Audrey D.; Anandakrishnan, Sridhar; Aster, Richard C.; Nyblade, Andrew A.; Wiens, Douglas A.
Abstract: We observe two (~ M S 3) long‐period (10–30 s) seismic events that originate from the terminus of Thwaites Glacier, Antarctica. Serendipitous acquisition of satellite images confirm that the seismic events were glacial earthquakes generated during the capsizing of icebergs. The glacial earthquakes were preceded by 6 days of discrete high‐frequency seismic events that can be observed at distances exceeding 250 km. The high‐frequency seismicity displays an increasing rate of occurrence, culminating in several hours of sustained tremor coeval with the long‐period events. A series of satellite images collected during this precursory time period show that the high‐frequency events and tremor are the result of accelerating growth of ancillary fractures prior to the culminating calving event. This study indicates that seismic data have the potential to elucidate the processes by which Thwaites Glacier discharges into the ocean, thus improving our ability to constrain future sea level rise. Plain Language Summary: Thwaites Glacier is one of the largest sources of Antarctic ice mass loss; however, the physics of the processes that control its discharge into the ocean remains incomplete. The long‐term stability of glaciers, such as Thwaites, that discharge directly into the ocean is linked to the rate of calving, the process of iceberg production. Spaceborne observations are crucial to understanding the calving processes; however, the typical repeat time of a satellite imagery is much longer than the typical duration of a calving event (minutes to hours). Increasingly, the seismic signals generated during calving are being used to complement other observations. For larger calving events, seismic energy can be recorded by remote seismic observation (hundreds to thousands of kilometers away from a glacier). While these glacier earthquakes are now regularly used to study calving in Greenland, only a limited number of glacial earthquakes have been observed in Antarctica. We show that Thwaites Glacier has now begun generating glacial earthquakes similar to those observed in Greenland. Additionally, we show that enhanced rates of fracturing can be seismically observed before the event. Our observations open a new avenue for understanding the behavior of Antarctica's leading source of mass loss. Key Points: Thwaites Glacier calving events generate seismic energy that can be detected at distances up to 1, 600 km Precursory seismicity reveals elevated rates of fracturing in the week leading up to calving Remote seismic observations can be used to study the calving processes of Thwaites Glacier